Potentially preventable dementia in a First Nations population in the Torres Strait and Northern Peninsula Area of North Queensland, Australia: A cross sectional analysis using population attributable fractions - Fintan Thompson; Sarah Russell; Rachel Quigley; Betty Sagigi; Sean Taylor; Malcolm McDonald; Sandy Campbell; Adrian Esterman; Linton R. Harriss; Gavin Miller; Edward Strivens; Robyn McDermott (Elsevier, 2022)
Summary: Background: Dementia is highly prevalent among Australia's First Nations peoples, including Torres Strait Islander and Aboriginal peoples in Far North Queensland (FNQ). It is likely that historically recent exposure to modifiable risk factors underlies these rates, and a large proportion of dementia may be potentially preventable. Methods: Data from two adult community health checks (2015-2018) were analyzed to determine the prevalence of 11 modifiable dementia risk factors among the First Nations residents of the Torres Strait and Northern Peninsula Area of FNQ. Population attributable fractions (PAF%) for dementia were calculated using age-standardized prevalence estimates derived from these health checks and relative risks obtained from previous meta-analyses in other populations. PAF% estimates were weighted for communality to account for overlap of risk factors. Findings: Half (52·1%) of the dementia burden in this population may be attributed to 11 potentially modifiable risk factors. Hypertension (9·4%), diabetes mellitus (9·0%), obesity (8·0%), and smoking (5·3%) were the highest contributing risk factors. The contribution of depression (2·0%) and alcohol (0·3%) was lower than other global and national estimates. While the adjusted PAF% for social isolation was low based on the adult community health check data (1·6%), it was higher (4·2%) when official census data were analyzed. Interpretation: These results suggest that a substantial proportion of dementia in FNQ First Nations peoples could potentially be prevented. Government investment in preventative health now is essential to reduce the future burden of dementia. Funding: National Health and Medical Research Council (NHMRC, GNT1107140, GNT1191144, GNT1106175, GNT0631947).